Curative cerebrovascular reconstruction with the Pipeline embolization device: the emergence of definitive endovascular therapy for intracranial aneurysms. (23rd July 2018) - Fiorella, D; Lylyk, P; Szikora, I; Kelly, M E; Albuquerque, F C; McDougall, C G; Nelson, P K
Abstract : Endovascular, endosaccular, coil embolization has emerged as an established therapy for both ruptured and unruptured cerebral aneurysms. However, many aneurysms are not cured using conventional endovascular techniques. Coil embolization often results in incomplete aneurysm occlusion or recanalization in the ensuing months after treatment. The Pipeline embolization device (PED; Chestnut Medical) represents a new generation endoluminal implant which is designed to treat aneurysms by reconstructing the diseased parent artery. Immediately after implantation, the PED functions to divert flow from the aneurysm, creating an environment conducive to thrombosis. With time, the PED is incorporated into the vessel wall as neointimal–endothelial overgrowth occurs along the construct. Ultimately, this process results in the durable complete exclusion of the aneurysm from the cerebrovasculature and a definitive endoluminal reconstruction of the diseased parent artery.